The inner life of the counselor - Wicks, Robert J. (Wiley, 2012)
"To feed the interior life of the counselor is not only a sensible act for the helper, it is a true act of generosity for those they serve as well. This book directs counselors to consider their own sense of self and how they are-and are not-living a personally and professionally meaningful, mindful life. Each chapter presents a theme in a way that mental health professionals will find helpful and immediately applicable to understanding their own journey as they seek to reach out to help others in need"--